The relationship of mindfulness breathing exercises to performance anxiety and vocal technique in high school choir - Tracy, Tabitha (My University, 2026)
A key component of mindfulness is the practice of breathing exercises. Few studies have examined the relationship between mindfulness-based breathing and improved singing technique. My objective was to study this response, particularly among students experiencing heightened performance anxiety, and to develop exercises that would promote positive mental agility. To begin this project, I conducted an informal survey of thirty-eight vocalists in our Advanced Treble and Chamber Choirs to understand their firsthand experiences of difficulties with breath support under performance pressure. Based on that information, I developed specific warm-ups for the two rehearsals leading up to our contest and concert performances. Each exercise stems from Mindfulness-Based Stress Reduction (MBSR) interventions, designed from the singer's perspective, focusing on sustaining long phrases, building breath awareness, and the performer's body alignment. Jon Kabat-Zinn, the developer and founder of Mindfulness-Based Stress Reduction, explains that mindfulness in education is the domain of being, rather than the domain of doing (Kabat-Zinn, 2013). At the conclusion of the performance cycle, students had the opportunity to share personal narratives reflecting on their experiences with mindfulness breathing. Through my newfound self-awareness, I have discovered the importance of intentionality when implementing these exercises. Mindful breathing supports focus and mental stamina, especially under the pressure of adjudicated performances. This takes students to a vulnerable place, and it is imperative to do so with authenticity as an educator. Additionally, it is promising that these mindfulness breathing exercises could promote the longevity of a healthier vocal singing technique when integrated with year-long curriculum goals. My design was to create a well-developed guide or series of lessons that incorporates the partnership between MBSR and vocal pedagogy, serving the whole-child body, mind, and breath. My development as a teacher during my Master’s program has transformed my philosophy and pedagogy. Attention to different learner modalities not only redesigned my rehearsal scaffolding and long-range planning, but also has helped me individualize instruction to meet students' needs as they become well-rounded young adults and musicians. My goal as an educator is to provide lifelong resources that enhance students' focus and support effective learning. During my study of vocal pedagogy, I wanted to explore methods for developing healthy singing techniques. The concepts we cover include isolating vocal faults, identifying them accurately, and establishing tools that choral directors can use to address them during rehearsal. This report illustrates how MBSR exercises and activities integrate with strategies that enhance both a singer's vocal production and emotional artistry. This is the culmination of my coursework and demonstrates the vision that drives my educational ideology.
Keywords: Mindfulness; Performance Anxiety; Social and Emotional Learning; Breathing Exercises; Vocal Technique